Diagnostic Yield of Ultrasonography in the Evaluation of Abdominal Tuberculosis (Medical Forum Monthly, 2024)
Objective: To determine the diagnostic value of ultrasonography in detection of abdominal tuberculosis.Study Design: Descriptive study.Place and duration of study: This study was conducted in the department of diagnostic radiology, Bolan Medical Complex Hospital, Quetta during the year march 2014 to Feb 2015.Materials and Methods: 206 patients were selected from Bolan medical complex hospital both from outdoor and indoor departments. Patients presented with clinical signs and symptoms and ultrasonography findings suggestive of abdominal tuberculosis excluding genitourinary TB. Doppler ultrasonography was used to conduct the study for the evaluation of abdominal tuberculosis. These findings were confirmed by ascitic fluid cytology, fine needle aspiration and response to response to anti TB drugs. Ultrasound was repeated in 1 month and second month.Results: The 206 patients were included in this study which comprises 103(50 %) male and 103(50 %) female with male to female ratio was (1:1) the mean age of patient was 35year. Low grade fever was present in 115(80%), weight loss 120 (58.53%), diarrhea 58 (31.70%) altered bowel habit 25 (12.19%) and abdominal pain and distension 176 (85.85%). Ultrasound findings include ascites 120 (58.53%), lymphadenopathy 78 (38.04%) bowel wall thickening 43 (20.97%), omental/peritoneal thickening 28 (13.65%), hepatomegaly 5 (2.43%) and splenomegaly 3 (1.46%)Conclusion: ultrasonography is non-invasive diagnostic tool, easily available and cost effective. Ultrasound would be effective tool in the diagnosis of abdominal tuberculosis. Where the other imaging modalities are expensive and not easily available